The flywheel paradigm in team sports: a soccer approach - Raya-González, J.; Castillo, D.; Beato, M. (Strength and Conditioning Journal, 2021)
Strength training is a key strategy to improve performance and injury prevention in team sports. Accordingly, several methods have been used, although because of the benefits reported after training based on eccentric contractions, the use of flywheel (FW) devices has extended within the periodization of strength training of team sports. However, nowadays, there is no clear consensus about the parameters used to optimize the training effects. This article examines the research behind these claims and attempts to draw evidence-based conclusions as to the practical implications for a precise use of FW with team-sport players, attending to their specific demands and objectives.